Konsekuensi Yuridis Berlakunya Perjanjian Perkawinan Pasca Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Ardhya, Si Ngurah; Mertha Sujana, I Putu Windu (Jurnal Komunikasi Hukum, 2021)
Philosophically PMK (Constitutional Court Decision) Nr. 69/PUU-XIII/2015 based on way of life, awareness, and legal ideals such as the mystical atmosphere and Indonesian Nation according Pancasila and The Constitutional of The Republic of Indonesia Article 28E Paragraph (2). Sociologically, based on legal needs society regarding the leniency when the marriage agreement was made that is the phenomenon of a husband and wife for some reason feels they needed to make a marriage agreement after the wedding day was held. Juridically, the issuance of PMK Nr. 69/PUU-XIII/2015 is not solely on the basis of unconstitutionality, but also on a conflict of norms between Article 29 Paragraph (1) of Act Nr.  Year 1974 with general provisions of the ageement in Book III Code of Civil Law. Referring to PMK No.69/PUU-XIII/2015 which was strengthened by Act Nr. 2 Year 2014, Notary has the right to ratified the marriage agreement into an authentic deed so that there is no justifiable reason for the Department of Population and Civil Registration and Office of Religious Affairs rejects the authentic nature of the deed which is validated bay notary.